Competitive position, managerial ties, and profitability of foreign firms in China: an interactive perspective - Li, Julie Juan; Zhou, Kevin Zheng; Shao, Alan T (Journal of International Business Studies, 2009)
Despite the prominence of the competitive strategy perspective, it remains unclear whether foreign firms entering China can still adopt a differentiation or low-cost position to achieve superior performance, given the unique market and institutional environments in China. Alternatively, should foreign firms follow conventional wisdom and actively build managerial ties with government officials and business community to enhance their performance? This study develops and tests an interactive perspective that highlights the moderating effects of managerial ties on competitive position–performance relationships. The results indicate that though both differentiation and low-cost positions foster foreign firm profitability, the benefit of a differentiation position is conditional on political and business ties in different directions: political ties impede and business ties strengthen the positive effect of a differentiation position on foreign firms' profitability. Moreover, foreign firms benefit from their use of business ties, but their profitability suffers when they rely increasingly on the heavy use of political ties.